Sealing Ability of Resin Based Root Canal Sealers: An In Vitro Study - Rijal, Sujan (Journal of Gandaki Medical College-Nepal, 2017)
The primary goal is to attain a three dimensional seal, which would lead to an impervious seal. Obturation of the prepared root canal eliminates all avenues of leakage from the oral cavity and the periodontal tissues, sealing any residual irritants that remain within the root canal system after cleaning and shaping. Though the primary goal of obturation has been clearly defined there is still an ongoing research for a sealer and a core material that would provide an apical as well as coronal seal.Journal of Gandaki Medical College Volume, 09, Number 2, July December  2016, Page: 58-62